2013
DOI: 10.2527/jas.2012-5821
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a Bacillus-based direct-fed microbial supplemented to sows on the gastrointestinal microbiota of their neonatal piglets

Abstract: Direct-fed microbials (DFM) supplemented in sow diets may confer health benefits to the host and their piglets by reducing pathogens in the sow and environment. In this study we evaluated the effect of a Bacillus-based DFM on the gastrointestinal microbiota of neonatal piglets. A total of 208 sows were divided into 2 treatments: a control diet and the control diet supplemented with a Bacillus subtilis-based DFM (3.75 × 10(5) cfu/g feed). Twenty-one piglets sampled from each sow treatment group were euthanized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
69
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 31 publications
8
69
1
Order By: Relevance
“…in ileum. There are numerous studies about probiotics which show higher lactobacillus colonization in intestine (Choi et al, 2011a and2011b;Baker et al, 2013). We had hypothesized an interaction between bacteriophages and probiotics, because bacteriophages have the ability of eliminating pathogens and give the opportunity to Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…in ileum. There are numerous studies about probiotics which show higher lactobacillus colonization in intestine (Choi et al, 2011a and2011b;Baker et al, 2013). We had hypothesized an interaction between bacteriophages and probiotics, because bacteriophages have the ability of eliminating pathogens and give the opportunity to Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…They cannot colonize in the gastrointestinal tract; but stimulate the growth of Lactobacilli through production of catalase and subtilisin (Hosoi et al, 2000). Several studies reported improvements in growth performance (Huang et al, 2004;Alexopoulos et al, 2004), nutrient digestibility (Shon et al, 2005;Chen et al, 2006), humoral and cell-mediated Ahmed et al 97 immune responses (Fernandes and Shahani, 1990; European food safety authority, 2010), and the microbial ecosystem (Huang et al, 2004;Baker et al, 2013) upon dietary supplementation with Lactobacillus or Bacillusbased probiotics, although inconsistencies in result have also been reported (Cromwell, 2001). The discrepancies observed can be attributed to different strains, dose levels, diet compositions, feeding strategies, age of animals, etc (Chesson, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In swine, litters from sows fed Bacillus subtilis (3.75 ϫ 10 5 CFU/g feed) exhibit greater weaning weight (14). Oral supplementation with B. subtilis spores increases the abundance of Lactobacillus species in the colon of pigs (14).…”
mentioning
confidence: 99%
“…In swine, litters from sows fed Bacillus subtilis (3.75 ϫ 10 5 CFU/g feed) exhibit greater weaning weight (14). Oral supplementation with B. subtilis spores increases the abundance of Lactobacillus species in the colon of pigs (14). Our previous studies using an E. coli model showed that pretreatment with certain probiotics, such as Lactobacillus rhamnosus or various Bacillus strains, ameliorates infectious enteritis or diarrhea in newly weaned piglets; however, there is a risk that high-dose probiotic pretreatment may negate the preventative effects (10,15).…”
mentioning
confidence: 99%